Three species of the isopod crustacean genus Antennuloniscus Menzies, 1962 (Asellota: Haploniscidae) from the Southern Ocean - Brökeland, Wiebke (Zootaxa, 2006)
The genus Antennuloniscus is rediagnosed and discussed. Antennuloniscus ornatus Menzies, 1962 and A. armatus Menzies, 1962 are redescribed and A. latoperculus n. sp. is described from material obtained from the Southern Ocean.